2007
DOI: 10.1007/s11101-006-9027-z
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents of the plants of the genus Cleistanthus and their biological activity

Abstract: Chemical examinations of Cleistanthus collinus Roxb., a poisonous tree from India, and Cleistanthus patulus Muell. Arg. have resulted in isolation of a number of arylnaphthalide lignans and their glycosides as well as some furofuranoid lignans. While Cleistanthus gracilis Hook. f. from Thailand afforded an unusual glucoside of 2-b-hydroxy-8-azabicyclo-(5,0,2)-4b, 9b-epoxynona-5,7-diene, C. schlechteri from South Africa was the first reported source of the pimarane diterpenes. Cleistanthin A and cleistanthin B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…5 Cleistanthins A and B are the two main active phytochemicals present in the most of the aerial parts of the plants. 6 Subsequent study with cleistanthin A and B on guinea pig vas deferens confirmed the blockade of phenylephrine induced contractions. 7 Phenylephrine shows selective agonism to alpha 1-adrenoceptor and the fact that cleistanthins A and B block the contractions induced by phenylephrine indicates that cleistanthins A and B have alpha 1-adrenoceptor blocking property.…”
Section: Introductionmentioning
confidence: 85%
“…5 Cleistanthins A and B are the two main active phytochemicals present in the most of the aerial parts of the plants. 6 Subsequent study with cleistanthin A and B on guinea pig vas deferens confirmed the blockade of phenylephrine induced contractions. 7 Phenylephrine shows selective agonism to alpha 1-adrenoceptor and the fact that cleistanthins A and B block the contractions induced by phenylephrine indicates that cleistanthins A and B have alpha 1-adrenoceptor blocking property.…”
Section: Introductionmentioning
confidence: 85%
“…Glycosides such as Cleistanthin A and B are the principle toxins isolated from this poisonous plant, as all parts of this plant is reported as highly toxic (Annapoorani et al, 1984). These cleistanthins have been reported to have anticancer property in vitro and in vivo and may have the probable to become lead compounds to treat cancer (Prabhakaran et There is a significant amount of arylnaphthalide lignans such as diphyllin, collinusin and many other related compounds present in the plant C. collinus (Pinho and Kijjoa, 2007;Satyanarayana et al, 1984). Cleistanthin A and B produce DNA strand breaks in in vitro studies by reducing the viability of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…However, only several species have been chemically studied so far. [1][2][3][4][5][6][7][8][9][10][11] The most popular plant of this genus is C. collinus due to its toxicity. The plants of the Cleistanthus genus are well known for their lignan and terpenoid content.…”
Section: Introductionmentioning
confidence: 99%
“…[1,[4][5][6][7][8][9] Among them, cleistanthin A and cleistanthin B isolated from C. collinus were found to exhibit preferential cytotoxicity in several tumor cell lines. [11][12][13] In our screening program on the flora of Vietnam, the plant C. indochinensis Merr. ex Croiz was collected from Nghe An province.…”
Section: Introductionmentioning
confidence: 99%